Conducive organizational infrastructure for training activities : a case study of the Nepalese construction sector - Bajracharya, Arun; Ogunlana, Stephen O.; Chotchai Charoenngam; Nguyen Luong Bach; Asian Institute of Technology Paitial Scholarship (Bangkok : Asian Institute of Technology, 1998)
Learning is the competitive advantage of an organization. But adverse organizational settings nullify and even oppose the learning processes. The Nepalese construction sector is also suffering with such adverse settings. In this study, organizational behavioral settings have been focused through system dynamics methodology to trace out the causes of the adversity. Dominating positive feed back loops (vicious cycles) with the OB variables are explored to be the underlying structures causing the adversity. Through simulation experiments, it has been observed that intuitive individual policy measures are rather ineffective to reform the organizational settings. Numerous model experiments revealed that the public sector needs proactive management effort along with values reformation policy to revert the adverse direction of the dominating vicious cycles, while the private sector needs to equip itself with proactive culture and entrepreneur values supported by favorable government policies for spacious domain to play their role. These directional policy framework has been observed to be promising in the long run. However, to corroborate the directional policy framework, operational policies are recommended for furthuer study in order to actualize the operational steps.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Manpower policy -- Nepal; Employees -- Training of -- Nepal